Entrepreneurial Marketing as a Key Strategy for the Sustainability of Tourism Businesses in POKDARWIS Gombengsari Banyuwangi's MSME’s - Kukuh Handojo; Sudarmiatin Sudarmiatin; Wening Patmi Rahayu (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
The purpose of this study is to determine the application of Entrepreneurial marketing in Gombengsari POKDARWIS MSMEs using a qualitative approach through in-depth interview methods at the manager of the Gombengsari POKDARWIS MSMEs. Researchers want to obtain an overview related to the application of the concept of Entrepreneurial marketing in ensuring business continuity in the tourism sector, especially wellbeing tourism as one of the leading tours in the Gombengsari Banyuwangi area. The concept of Entrepreneurial marketing as a strategy that combines skills and understanding of entrepreneurship and marketing as a whole related to creative and unplanned marketing activities in an increasingly competitive and unstable business environment so that it is expected that Entrepreneurial marketing will be one of the main factors in maintaining and developing strategies for business continuity in the tourism sector which is very vulnerable to changes both social and economic and political. Based on interviews and findings at POKDARWIS Gombengsari MSMEs, the application of entrepreneurial marketing really helps these MSMEs to survive and bounce back after experiencing a decline and even a vacuum during the pandemic by combining creativity and understanding of consumers who have visited, a new program is created that is more attractive to tourists who have never previously offered the new program. Keyword : Entrepreneurial marketing, business sustainability, wellbeing tourism